Presupposition as a means of linguistic manipulation in Spanish political and journalistic discours - M. V. Larionova (Vestnik MGIMO-Universiteta)
The article analyzes the role of presuppositions, which are widely used in the Spanish political and journalistic discourse as a means of manipulating language, and are focused on strengthening the management capacity of language to provide a hidden impact on recipients. Presuppositions implicitly convey information; they are convenient and effective means of imposing a particular point of view, alien description and vision of reality. Presuppositions impose situation and action assessment, which does not coincide with the one that recipients of the information could form on their own.